Genetic association of the polymorphisms in apoptosis-related genes with osteoarthritis susceptibility in Chinese Han population - Ma, Gang (Int J Clin Exp Pathol, 2018)
Background: Apoptosis is a normal physiological process in organs development, but excessive apoptosis is pathological and harmful. In previous studies, apoptosis-related genes are considered to be involved in the onset of osteoarthritis, but the mechanism is unclear. Therefore, we selected two common polymorphisms of apoptosis-related genes (BAX -248G>A, BCL2 -717C>A) to explore the relationship with osteoarthritis. Methods: The two polymorphisms were genotyped by polymerse chain reaction-restriction fragment length polymorphism (PCR-RFLP) in 134 cases with osteoarthritis and 142 controls. These genotypes distributions in controls were checked whether conformed to Hardy-Weinberg equilibrium (HWE). χ(2) test was used to calculate odds ratio (OR) with corresponding 95% confidence interval (95% CI) which evaluated the strength of association between gene polymorphism and osteoarthritis susceptibility. Results: The χ(2) test showed that genotype frequencies of BAX -248G>A (rs4645878), BCL2 -717C>A (rs2279115) polymorphisms in control group were consistent with HWE. In BAX -248G>A polymorphism, compared with mutant genotype GA+AA, the common genotype GG increased the susceptibility to osteoarthritis significantly (OR=1.84, 95% CI=1.13-3.00), so G allele was (OR=1.76, 95% CI=1.16-2.68). The homozygous mutant genotype AA in BCL2 -717C>A carriers easily suffered from osteoarthritis in some condition, compared with CC genotype (P=0.03). A allele also increased 0.43 times risk of osteoarthritis development than C allele (OR=1.43, 95% CI=1.02-2.00). Conclusions: BAX -248G>A and BCL2 -717C>A polymorphisms may be the independent risk factors for the development of osteoarthritis.